Whole-Exome Sequencing Implicates the USP34 rs777591A > G Intron Variant in Chronic Obstructive Pulmonary Disease in a Kashi Cohort - Xu, Jingran; Li, Li; Ren, Jie; Zhong, Xuemei; Xie, Chengxin; Zheng, Aifang; Abudukadier, Ayiguzali; Tuerxun, Maimaitiaili; Zhang, Sujie; Tang, Lifeng; Hairoula, Dilare; Zou, Xiaoguang (Frontiers in Cell and Developmental Biology, 2022)
Genetic factors are important factors in chronic obstructive pulmonary disease (COPD) onset. Plenty of risk and new causative genes for COPD had been identified in patients of Chinese Han population. In contrast, we know considerably little concerning the genetics in the Kashi COPD population (Uyghur). This study aims at clarifying the genetic maps regarding COPD susceptibility in Kashi (China). Whole-exome sequencing (WES) was used to analyze three Uyghur families with COPD in Kashi (eight patients and one healthy control). Sanger sequencing was also used to verify the WES results in 541 unrelated Uyghur COPD patients and 534 Uyghur healthy controls. WES showed 72 single nucleotide variants (SNVs), two deletions, and small insertions (InDels), 26 copy number variants (CNVs), and 34 structural variants (SVs), including g.71230620T>A (rs12449210T>A, NC_000016.10) in the HYDIN axonemal central pair apparatus protein (HYDIN) gene and g.61190482A>G (rs777591A>G, NC_000002.12) in the ubiquitin-specific protease 34 (USP34) gene. After sanger sequencing, we found that rs777591“AA” under different genetic models, except for the dominant model (adjusted OR = 0.8559, 95%CI 0.6568–1.115, P > 0.05), could significantly reduce COPD risk, but rs12449210T>A was not related to COPD. In stratified analysis of smoking status, rs777591“AA” reduced COPD risk significantly among the non-smokers group. Protein and mRNA expression of USP34 in cigarette smoke extract-treated BEAS-2b cells increased significantly compared with those in the control group. Our findings associate the USP34 rs777591“AA”genotype as a protector factor in COPD.